A cross-cultural exploration of the everyday social participation of individuals with autism spectrum disorders in Australia and Taiwan: An experience sampling study. (February 2017) - Chen, Yu-Wei; Bundy, Anita C; Cordier, Reinie; Chien, Yi-Ling; Einfeld, Stewart L
Individuals with an autism spectrum disorder commonly have limited social participation. This study aimed to examine the similarities and differences of everyday participation among males and females with autism spectrum disorder in Australia and Taiwan, using an experience sampling methodology. A total of 14 Australians (4 males, aged 16–43 years) and 16 Taiwanese (12 males, aged 19–45 years) with autism spectrum disorder who are cognitively able were asked to carry a device which prompted them seven times per day for 7 days, to record everyday participation: where they were, what they were doing, and who they were with. Multilevel analyses were used to identify the relationships between everyday participation and associated factors including gender, country of residence, clinical severity of autism spectrum disorder, and social anxiety. The results showed that Taiwanese participants were more likely to stay at home than Australian participants. However, female participants were more likely to engage in social situations than males. Furthermore, participants with fewer autism spectrum disorder symptoms and those with higher levels of social anxiety were less likely to engage in social interactions. This study sheds light on ways that culture and gender affect social participation and highlights the relationship of social anxiety to social participation. The findings have implications for interventions for social participation.